The effect of ankle brace use on a 3-step volleyball spike jump height - You, D. Z.; Tomlinson, M.; Borschneck, G.; Borschneck, A.; MacDonald, M.; Deluzio, K.; Borschneck, D. (Arthroscopy, Sports Medicine, and Rehabilitation, 2020)
Purpose: The purpose of this study was to determine whether ankle brace use in university-level varsity volleyball athletes affected their 3-step spike jump height and whether certain types of ankle braces have a greater effect on jump height. Methods: Nine male university-level varsity volleyball athletes participated in a repeated-measures design study in which each athlete performed three 3-step volleyball spike jumps in 3 ankle brace conditions (soft, rigid, and no brace). Vertical jump height was measured by the Vertec device and video motion analysis at a university biomechanics research laboratory. Results: Vertical jump heights were significantly lower in both brace conditions (soft, 2.3 cm, standard deviation [SD] 1.2 cm, P < .001; rigid, 1.7 cm, SD 0.9 cm, P < .003) compared with the no-brace condition, and no differences in vertical jump height were observed between the brace conditions (0.6 cm, SD 0.3, P = .3). There was a negative correlation between body fat percentage and vertical jump height (r = -0.075, P = .02). The Vertec device reliably measured vertical jump in all 3 conditions. The no-brace vertical ground reaction forces during the loading phase were significantly greater than brace conditions. Ankle range of motion was greatest in the no-brace condition. Conclusions: Results from this study suggests that high-performance athletes wearing ankle braces experience a significant decrease in vertical jump height independent of the type of ankle brace worn. Clinical Relevance: Sports physicians and health care providers caring for high-level athletes should counsel athletes on the trade-offs of wearing protective equipment in sport, as potential decreases in sports performance can lead to increased injury prevention. Level of Evidence: III.